YIELD AND WEED FLORA OF WHEAT (TRITICUM AESTIVUM) AS INFLUENCED BY TILLAGE OPTIONS AND FERTILITY LEVELS UNDER RAINFED TEMPERATE CONDITION - SINGH, UMMED; SAAD, A.A.; SINGH, S.R.; SHARMA, L.K. (Annals of Agricultural Research, 2014)
A field experiment was carried out during winter seasons of 2006-07 and 2007-08 at the research farmof Faculty of Agriculture and Regional Research Station, Wadura, Sopore (J&K) to evaluate the relative performance of various tillage options and fertility levels in wheat after rice harvest. Among various tillage practices reduced tillage recorded markedly higher dry matter production and yield attributes (spike/m2, grains/spike, spike length and 1 000 grain weight). Reduced tillage resulted in the highest yield of 3.5 t/ha. The reduced tillage was the best option and recorded highest net return (Rs 28 325/ha), followed by rotary (Rs 24 695/ha) and zero tillage (Rs 21 975/ha) and least with conventional tillage (Rs 18 910/ha). Markedly higher uptake of N, P and K was also recorded with reduced tillage followed by rotary tillage. Lowest weed count and dry weight was recorded under conventional tillage and greatest under zero tillage. Application of 100% recommended dose of fertilizer (60 kg N, 40 kg P2O5and 20 kg K2O) recorded significantly higher dry matter accumulation, spike/m2 grains/spike, spike length, 1,000 grain weight and grain (3.4 t/ha) and straw yield over lower fertility levels but remained on par with 125% recommended dose of fertilizer. Similarly, net return/rupee investment increased significantly up to 100% recommended dose of fertilizer. Application of 125% of the recommended dose of fertilizer recorderd significantly higher weed count, weed dry bio mass and N, P and K uptake by crop than recommended 75% and 50% of the recommended dose of fertilizer.